Improvement Of Cultural Life And Education In The Cities Of Southern Regions (Eurasian Journal of Humanities and Social Sciences, 2024)
This article aims to study the development of cities in the south of Uzbekistan, to determine the dynamics of urban population growth and its specific aspects, as well as to study the socio-economic and cultural life of cities in the context of historical science. To substantiate the combination of traditionalism and transformational features in the urban planning culture of the southern regions and the general and local characteristics of this process. By comparing the cities of the southern regions with the cities of other regions of the republic, the following issues are raised: to summarize the achievements and accumulated experience in urban planning culture in our country, based on the explanation of their specific aspects.